THE USE OF MULTIMEDIA ANIMATION FOR IMPROVING STUDENT LEARNING OUTCOMES AT VOCATIONAL EDUCATION OF REFRIGERATION AND AIR CONDITIONING - Tasyarahmanto, Benido; Kusuma, Inu Hardi; Berman, Ega Taqwali (Universitas Pendidikan Indonesia, 2020)
The purpose of this research is to find out the improvement of student learning outcomes after using multimedia animation in the subjects of refrigeration and air conditioning control. This research was conducted in class XII TPA, Refrigeration and Air Conditioning Expertise Program at SMKN1 Cimahi. The sample used was 30 students and classroom action research was used as a research method. Learning activities carried out as many as three cycles consisting of planning, implementation, observation, and reflection. Collecting data on learning outcomes is done by carrying out pre-test and post-test. Improved student learning outcomes are measured by the value of N-Gain. The results showed the value of N-Gain in cycle I and cycle II were 0.51 and 0.59, respectively. These results are in the medium category. In cycle III there was an increase in the value of N-Gain by 24% to 0.73 and included in the high category. This research has implications for increasing learning activities and students' ability to understand refrigeration and air conditioning control materials that are getting better.